The Impact of COVID-19 upon Intracardiac Hemodynamics and Heart Rate Variability in Stable Coronary Artery Disease Patients - Netiazhenko, Vasyl Z.; Mostovyi, Serhii E.; Safonova, Olha M. (Ukrainian Journal of Cardiovascular Surgery, 2023)
The aim. To study the impact of COVID-19 upon intracardiac hemodynamics and heart rate variability (HRV) in stable coronary artery disease (SCAD) patients. Materials and methods. In this cross-sectional study we analyzed clinical and instrumental data obtained from a sample of 80 patients. The patients were divided into three groups: group 1 included patients with SCAD without COVID-19 (n=30), group 2 included patients with SCAD and COVID-19 (n=25), and group 3 included patients with COVID-19 without SCAD (n=25). The control group included 30 relatively healthy volunteers. Results. The changes in intracardiac hemodynamics and HRV in group 2 were characterized by the impaired left ventricular systolic and diastolic function, dilation of both ventricles and elevated systolic pulmonary artery pressure. Left ventricular end-diastolic volume was higher in group 2 (205±21 ml) than that in group 1 (176±33 ml; р<0.001) and group 3 (130±21 ml; р<0.001). Patients in the groups 1–3, compared to controls, presented with the decrease in the overall HRV (by standard deviation [SD] of all NN intervals [SDNN]; SD of the averages of NN intervals in all 5 min segments of the entire recording; and mean of the SDs of all NN intervals for all 5 min segments of the entire recording) and parasympathetic activity (root-mean-square difference of successive NN intervals; the proportion derived by dividing the number of interval differences of successive NN intervals greater than 50 ms [NN50] by the total number of NN intervals [pNN50], and high frequency spectral component), along with QT interval prolongation and increase in its variability. Group 2 demonstrated the most advanced changes in HRV (by SDNN and pNN50) and both QT interval characteristics. Conclusions. The patients with SCAD and concomitant COVID-19, along with both ventricles dilation and intracardiac hemodynamics impairment, presented with the sings of autonomic dysfunction, QT interval prolongation and increase in its variability. The heart rate variability and QT interval characteristics should be additionally considered in the management of such patients.